KINERJA PEMERINTAH DLAM PELAKSANAAN URUSAN OTONOMI DAERA DI DISTRIK KEMBU KABUPATEN TOLIKARA - WENDA, YANI; ROMPAS, WELSON; RURU, JOORIE MARHAEN (JURNAL ADMINISTRASI PUBLIK, 2019)
The purpose of this study was to determine the performance of the Tolikara District Kembugovernment in the implementation of regional autonomy. This research uses a descriptive-qualitativeapproach. Based on the study of theory, performance is seen from three dimensions or indicators, namely:productivity (effectiveness and efficiency), responsibility, and accountability. Research informants werethe Camat, the District Secretary, 2 Section Heads, and 1 Implementing Staff, and 2 Village Heads. Thedata analysis technique used is an interactive model analysis of Miles and Hubernann. The resultsshowed: (1) The performance of the Kembu District government in the implementation of regionalautonomy affairs in terms of productivity indicators (effectiveness and efficiency) is quite good. (2) Theperformance of the Kembu District government in the implementation of regional autonomy matters seenfrom the indicators of responsiveness is also quite good. (3) The performance of the Kembu Districtgovernment in the implementation of regional autonomy matters seen from the accountability indicatorsis quite good. Based on these conclusions this study recommends Increase the number of employees, andimprove the quality of employee HR.Keywords: Performance, Regional Autonomy Affairs, District Government.